Analysis of Rewetting Time and Temperature Distributions During Cooling Process in Vertical Rectangular Narrow - IGN. Bagus Catrawedarma; Indarto Indarto; Mulya Juarsa (Jurnal Energi Dan Manufaktur, 2013)
AbstractCooling process to analyze effect of gap size to rewetting time and temperature distributionswere studied from transient temperature of surface plate. It as result of experiment using twovertical plate with the initial temperature about 600°C. Debit and temperature of cooling waterare 0,09 L/s and saturated temperature. The gap sizes were changed from 1 mm, 2 mm, and 3mm. As the results showed that the smaller the gap size, the longer the rewetting time. Patternof temperature distribution is similar at initial condition for all of gap sizes and the smaller thegap sizes, the longer the time of decreasing temperature.Keywords: Cooling process, rewetting time, temperature distribution.AbstrakProses pendinginan untuk menganalisa pengaruh ukuran celah terhadap waktu pembasahandan distribusi temperatur diamati dari transient temperatur permukaan plat. Penelitiandilakukan menggunakan dua plat vertikal dengan temperatur awal 6000C. Debit dan temperaturair pendingin adalah 0,09 L/s dan temperatur jenuh. Ukuran celah divariasikan dari 1 mm, 2mm dan 3 mm. Hasil penelitian menunjukkan bahwa semakin kecil ukuran celah semakinpanjang waktu rewetting. Pola distribusi temperaursama pada kondisi awal untuk semuaukuran celah, semakin kecil ukuran celah semakin panjang waktu untuk penurunantemperatur.Kata kunci: Proses pendinginan, rewetting time, distribusi temperatur